Architectural Design Characteristics, Uses, and Perceptions of Community Spaces in Permanent Supportive Housing. Issue 1 (March 2020) - McLane, Yelena; Pable, Jill
People experiencing homelessness often face recoveries complicated by mental disability, substance abuse, and trauma. They can withdraw into self–imposed isolation and avoid important support services, making recovery more difficult. Affirmative relationships developed in part within the designed settings of transitional housing may play a significant role in countering these tendencies. The presence and effectiveness of communal gathering spaces in supportive housing must be better understood as a design problem, particularly given users' diverse ages, ethnicities, and health needs, which effectively inclusive environments must accommodate. In recent decades, architecture as a discipline has pivoted toward more human–centered approaches, with the individual's dignity and well–being at center stage. This study applies social science–based research methods and spatial analytics to the end of understanding how specific interior spaces, key to the recovery process, might be improved. The authors posit that the success of resident gathering spaces intended to prompt and support resident relationships and decrease users' feelings of marginalization may be influenced by a range of sociospatial design factors (i.e. visibility and ease of access, adjacencies, access to daylight and views, furniture types, and aesthetics) together with facility policies and events programming. The authors use a combination of space syntax, surveys, and qualitative methods to analyze two contrasting layouts in supportive housing locations in the UK and Florida, drawing conclusions intended to steer the development of typologies for similar facilities.